Polymorphisms of HOMER1 gene are associated with piglet splay leg syndrome and one significant SNP can affect its intronic promoter activity in vitro - Sutong Xu; Xingjie Hao; Min Zhang; Kai Wang; Shuaifeng Li; Xing Chen; Liaohan Yang; Lin Hu; Shujun Zhang (BMC Genetics, 2018)
Abstract Background In our previous genome-wide association study (GWAS) on the piglet splay leg (PSL) syndrome, the homer scaffolding protein 1 (HOMER1) was detected as a candidate gene. The aim of this work was to further verify the candidate gene by sequencing the gene and find the significantly associated mutation. Then we preliminarily analyzed the effect of the significant SNP on intronic promoter activity. This research provided a reference for further investigation of the pathogenesis of PSL. Result We investigated the 19 SNPs on HOMER1 and found 12 SNPs significant associated with PSL, including 8 SNPs resided in the potential intronic promoter region in intron 4. The − 663~ − 276 bp upstream the exon 5 had promoter activity and it could be an intronic promoter that regulated the transcription of HOMER1–205 transcript. The promoter activity of the − 663~ − 276 bp containing the rs339135425 and rs325197091 mutant alleles was significantly higher than of the wild type (P < 0.05). The G allele of rs325197091 (A > G) may create a new binding site of transcription factor aryl hydrocarbon receptor nuclear translocator (ARNT) and could enhance HOMER1 intronic promoter activity. Conclusions HOMER1 gene was associated with the PSL, and the rs325197091 could influence HOMER1 intronic promoter activity in vitro.